Maternal age at delivery and fertility of the next generation. Issue 6 (9th March 2020) - Reynolds, Tamara S.; Lynch, Courtney D.; Hade, Erinn M.; Allain, Dawn C.; Westman, Judith A.; Toland, Amanda E.
Abstract: Background: While most known causes of infertility relate to the health of the woman and/or her partner, questions have been raised regarding the possible contributions of transgenerational or epigenetic factors. Objective: The goal of this hypothesis‐generating work was to examine whether Generation 1's (G1's) age at the delivery of G2 (Generation 2) was associated with G2's fertility in later life. Methods: We conducted a retrospective cohort study of women (G2s) recruited online in 2016. A questionnaire queried G2s regarding demographics and fertility. The primary exposure was G1's age at G2's birth. Outcome measures included the following: 12‐month infertility, time to pregnancy, and childlessness. The adjusted relative risk (RR) of G2 infertility and childlessness by G1 age at G2's birth was estimated through a modified Poisson regression approach. The fecundity odds ratio (FOR) for the association between G1's age at G2 birth and time to pregnancy for G2 was estimated by discrete‐time survival models, with complementary log–log link. Results: A total of 2, 854 women enrolled. We found no association between G1 age at G2's birth and G2 infertility. Being born to a G1 aged 15‐19 years was associated with a longer time to pregnancy for G2 (FOR 0.84, 95% confidence interval 0.72, 0.99), relative to being born to a G1 aged 20‐24 years. We observed the suggestion of a possible increased risk of childlessness among G2s born to older G1s, but the estimate was imprecise. Conclusions: While being born to a G1 who was 15‐19 years old was associated with an increase in G2 time to pregnancy, we found no association between G1 age at G2's birth and infertility and only the suggestion of a modest association with childlessness. These data suggest a possible subtle effect of G1 age at G2's birth on G2 fertility, which warrants further study.